Effectiveness of Instructional Program in Midwife’s Performance Regarding Second and Third Stages of Labor in Delivery Room - Maha Salah Razzaq,; Mauna Kouira,; Shukriyia Shadhan Chyad Al- Ogaili, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Midwives are essential in providing effective and safe care to women during labor. Midwifery care is associated with a variety of positive outcomes for mother and child. However, midwives also face many challenges, including a lack of human resources and dealing with complex deliveries. Objective: Assess the effectiveness of an educational program in improving the performance of midwives in intrapartum care in the delivery room. Methodology: A quasi-experimental design was carried in Al-Najaf Health Directorate/Al-Zahra and Al-Hakeem Teachings Hospitals; the study was conducted from March 20th , 2024 to June 25th, 2024. A purposive sample consisted of 70 midwives, 35 midwives who were exposed to the educational program sessions were considered as a study group, and 35 midwives considered as the control group and who were not exposed to the program. Conclusion and Recommendation: The majority of the studied sample had moderate performance in the pre-test, whereas there was an improvement in midwives' performance after exposure to program sessions for the study group. The study emphasizes the need for ongoing education and training sessions to maintain and further enhance midwives' skills in this critical area of obstetric care.